CONTENT AND CONCEPTUAL BASIS OF THE PRINCIPLE OF PATRIOTISM IN UNDERSTANDING NATIONAL IDENTITY (Scientific journal of the Fergana State University, 2025)
Today, members of the society respect the history and fate of the country, the people they belong to, the way of life, values, and traditions of the community, strata or different social classes they belong to. , it is important to teach people to understand the sense of homeland and national identity. This article analyzes the principles and their conceptual bases aimed at improving the approach to the issue of national identity and loyalty based on the principle of patriotism. The essence of the principle of patriotism is revealed.